Vascular Niche in Lung Alveolar Development, Homeostasis, and Regeneration - Mammoto, Akiko; Mammoto, Tadanori (Frontiers in Bioengineering and Biotechnology, 2019)
Endothelial cells (ECs) constitute small capillary blood vessels and contribute to delivery of nutrients, oxygen and cellular components to the local tissues, as well as to removal of carbon dioxide and waste products from the tissues. Besides these fundamental functions, accumulating evidence indicates that capillary ECs form the vascular niche. In the vascular niche, ECs reciprocally crosstalk with resident cells such as epithelial cells, mesenchymal cells and immune cells to regulate development, homeostasis and regeneration in various organs. Capillary ECs supply paracrine factors, called angiocrine factors, to the adjacent cells in the niche and orchestrate these processes. Although the vascular niche is anatomically and functionally well characterized in several organs such as bone marrow and neurons, the effects of endothelial signals on other resident cells and anatomy of the vascular niche in the lung have not been well explored. This review discusses the role of alveolar capillary ECs in the vascular niche during development, homeostasis and regeneration.